Combination of Piper betel Leaves and Areca catechu Nuts Ethanolic Extract Effects on In Vitro Antimicrobial Test against Aerobic Mouth Microbiota - Christanto, Raymond; Andre, Andre; Foustine, Shania; Hartiadi, Leonny Yulita (Indonesian Journal of Life Sciences, 2019)
Introduction: Oral health awareness in Indonesia is still low with more and more oral and/or dental infection becomes more prevalent such as gingivitis, endodontitis, and pericoronitis. These infections could be caused by mouth microflora such as lactobacilli, Streptococcus mutans, Streptococcus mitis, Streptococcus oralis, and Streptococcus sobrinus. As time goes by, these bacteria could also become more problematic as antibacterial resistance emerges. Betel nut and betel leaf are well known traditional herbs that is often used in combination for "nyirih"; an Indonesian tradition to chew both plants often after meal. It is believed that these plants treat bad breath and also increases oral health as it could inhibit bacterial growth. Method: Betel nut and betel leaf were dried, powdered and macerated using 96% ethanol. The extract was tested on mouth microflora of volunteers grown in BHI using agar using disk diffusion test and modified E-test strip. Results: The betel leaves extract showed antibacterial activity in most of concentration used (1.25%, 2.5%, 5%, 10%) while betel nuts only gave antimicrobial effect in 10% concentration. The E-test results also showed the synergistic action between Piper betel leaves and Areca catechu nuts with some giving significant difference compared to the single treatment (P<0.05). Conclusion: Piper betel leaves gives antimicrobial effect with MIC value of 1.25% while Areca catechu have MIC value of 10%. Furthermore, combination of both resulted in synergistic effect as indicated with larger diameter of inhibition compared to the single treatments.